Improving Children's Gross Motor Development Through Outdoor Obstacle Play - Bella Nadya Lusiana Hutabarat; Mimpira Haryono; Ela Pebriani (Journal Of Dehasen Educational Review, 2026)
This study aimed to improve the gross motor development of Group B children through outdoor obstacle course play at TK S PTPN 7 Sukaraja, Seluma Regency. The study employed a Classroom Action Research (CAR) method using the John Elliot model, which was conducted in two cycles consisting of planning, action, observation, and reflection. The research participants were 15 children, comprising 8 boys and 7 girls. Data were collected through observation, documentation, and field notes, while data analysis was conducted using descriptive quantitative and descriptive qualitative techniques. The findings revealed that the children's gross motor development improved in each cycle. The percentage of gross motor development in Cycle I reached 64.44%, categorized as Developing as Expected, and increased to 92.00% in Cycle II, categorized as Very Well Developed. Therefore, it can be concluded that outdoor obstacle course play is effective in improving the gross motor development of Group B children at TK S PTPN 7 Sukaraja, Seluma Regency.